The Managing Role in Creating Cultures of Innovation and Team Creativity - Nur Özkaya, Zeynep; Ismail, Aminah Binti; Mardikaningsih, Rahayu (Journal of Social Science Studies, 2023)
Innovation and creativity are key factors in the successful of organizations that are able to adapt to fast-changing market dynamics. Managers play an important role in creating a culture of innovation that can facilitate creativity within the team. This study examines how managers can create an environment that supports innovation and creativity by providing freedom of thought, space for experimentation, and respect for the contributions of each individual in the team. Managing creative teams requires clear structures, focused objectives, and policies that encourage collaboration, diversity and open communication. The right approach to managing creative teams can increase the spirit of collaboration, build a sense of shared responsibility, and accelerate the creation of relevant new ideas. As such, effective managers can help organizations achieve successful by creating an innovative and productive culture. Implementing these principles consistently will resulting in a team that is competitive and able to adapt to change.